The Evaluation of the Finnish Self Government Experiment - Kari Hamalainen (European Regional Science Association (ERSA), 2011)
This paper evaluates the cost effects of a regional self government experiment. The experiment introduced a new intermediate tier of local administration that was given the responsibility to organize 60 per cent of public services. These services include e.g. basic health care, majority of social services and secondary education that are typically produced by municipalities in Finland. Follow-up reports suggest that the experiment has resulted in massive cost saving, especially in the social and health sectors. This paper puts previous findings under scrutiny by utilizing latest econometric evaluation methods developed for comparative case studies. Our findings cast serious doubts on the magnitude of cost savings.
Keywords: 330